Contributing Factors to Customer Loyalty in Fast-Food Restaurants: A Study of KFC - Varsha Ganatra; Kok Ban Teoh; Nur Batrisyia Sapian; Daisy Mui Hung Kee; Nur Aqilah Mas Ud; Nur Darwisyah Zulkepli; Nur Farhah Fadhilah Mokhtar; Kavita Jaiswar (Advances in Global Economics and Business Journal, 2021)
KFC is known globally as one of the largest fast-food chains. It raises the issue of how they managed to survive years after years, although the fast-food industry's rivalry has grown rapidly with many leading brands in the market. For KFC to survive the severe competition, they need to retain the values that keep their loyal customers. This research aims to investigate the contributing factors to customer loyalty. A total of 100 respondents from Malaysia have participated in the survey. The results indicated that food quality, convenience, and price and value are the important factors that lead to customer loyalty. The findings may be useful for the management of KFC Malaysia to sustain their business through the competitive industry.